The Linkage Between Coenzyme A Metabolism and Inflammation: Roles of Pantetheinase - Takeaki Nitto; Kenji Onodera (Elsevier, 2013)
Pantetheinase is an enzyme hydrolyzing pantetheine, an intermediate of the coenzyme A degradation pathway. Pantetheinase has long been considered as the enzyme that recycles pantothenic acid (vitamin B5) generated during coenzyme A breakdown. Genetic analyses showed that mammals have multiple genes known as vanin family genes. Recent studies using mice lacking the vanin-1 gene (pantetheinase gene) suggest that pantetheinase is actively involved in the progression of inflammatory reactions by generating cysteamine. Additional studies using human leukocytes demonstrate that human neutrophils have abundant pantetheinase proteins on the surface and inside the cells. The second pantetheinase protein, GPI-80/VNN2, is suggested to work as a modulator of the function of Mac-1 (CD11b/CD18), an adhesion molecule important to neutrophil functions. This review delineates the characteristics of the pantetheinase/vanin gene family and how they affect inflammation. Keywords:: inflammation, pantetheinase, cysteamine, neutrophil, oxidative stress